2013
DOI: 10.1111/hepr.12066
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy of natural human interferon‐beta and ribavirin for chronic hepatitis C patients with injection drug use

Abstract: IFN-β/RBV combination therapy is useful for treating IDU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Previous studies reported that HCV‐2 or 3, but not HCV‐1, was prevalent among PWID in the main islands of Japan . These data suggest that HCV‐2/3 infection occurred by another distribution channel of illegal drugs in the main islands of Japan.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Previous studies reported that HCV‐2 or 3, but not HCV‐1, was prevalent among PWID in the main islands of Japan . These data suggest that HCV‐2/3 infection occurred by another distribution channel of illegal drugs in the main islands of Japan.…”
Section: Discussionmentioning
confidence: 65%
“…Furthermore, we speculate that IDU might have been the driving Previous studies reported that HCV-2 or 3, but not HCV-1, was prevalent among PWID in the main islands of Japan. [40][41][42][43][44] These data Although the MSM population was not included in our study, it has been reported that the number of HIV cases among MSM has increased in Okinawa. 48 The HCV transmission network among MSM is international 45,49,50 and MSM tourists visit Okinawa from other areas in Japan or overseas.…”
Section: Discussionmentioning
confidence: 92%
“…G1b, 31 %; Others: G2, G4, G5 [72,[103][104][105][106][107][108][109][110][111] CC/CT/TT-61.1/30.5/ 8.4, [112] Japan 127. 29 [115] 1.5-2.0 (1-2 %) [116,117] Blood transfusion (before 1992) [118][119][120], tattooing [121], intravenous drug abuser [122], needle stick [123] G1b, 70 %; G2a, 20 %; G2b, 10 % [126][127][128] 70-80/20-30 [132] Turkey 74.526 [192] 0.4-1.0 [193,194] Surgery, blood transfusion [195] G1b, 84 %; G1a, 10 %; G2, 3 %; G3, 1 %; G4, 1 % [196,197] 50 -31 [198] a,b…”
Section: Bangladesh Prevalence Of Hcv Infectionmentioning
confidence: 99%
“…Tattooing and illegal intravenous drug users are at risk of HCV infection in Japan as well as in other countries [121,122]. Although an effective vaccine against HCV is not available at present, HCV infections from needle sticks during health care procedures including persons with medical and dental activities [123], mother-to-child transmission [124] and transmission between husband and wife [125] are occasionally reported.…”
Section: Risk Factors Of Hcv Infectionmentioning
confidence: 99%